Energy efficiency and its influencing factors: a case study - Junfeng Zhang (2020)
© 2020, © 2020 Taylor & Francis Group, LLC. Analysis of the energy efficiency and productivity evolution of manufacturing are conducive to updating the structure of industry and enhancing the development of low-carbon economy for Shandong province in China. Based on Super-slack-based measure model and Malmquist-Luenberger productivity index, the energy efficiency and the evolution of productivity of 24 subsectors of Shandong’s manufacturing industry are evaluated during 2006–2015. Then, panel regression model is adopted to further investigate influencing factors of total factor productivity. The results include three key points: (1) The growth rate of annual average in energy efficiency is 1.5%. And there are significant disparities among 24 subsectors of manufacturing industry. The light manufacturing has better potential for energy efficiency improvement in manufacturing industry. (2) The productivity evolution of light manufacturing is promoted by technical change and efficiency change. For heavy manufacturing, efficiency change exerts a negative effect while technical change improves the growth of total factor productivity. (3) Trade, environmental regulation and private enterprises have positive effect on total factor productivity of light manufacturing while energy intensity and state-owned enterprises take negative effect on total factor productivity of manufacturing industry.